Impact of the Anti-Intellectual Attitudes to the Level of Self-Esteem of Senior High School Students from Fiat Lux Academe-Cavite, Philippines - Cristine Kyle Cuizon; Mary-Ann Atienza; John Ismael Medina (Philippine Association of Institutions for Research, Inc., 2018)
Anti-intellectualism, the manifestation of disrespect and lack of interest of individuals for intellectual pursuits and critical thinking, has become a constant thread not only in the corporate world but also among students. Its long-term effect will be very excruciating, especially in the Philippine economy. This quantitative correlational research investigated the extent of relationship between the anti-intellectual attitudes and level of self-esteem or the individual's overall sense of self-worth or personal value of one hundred and ninety-four (194) senior high school students from Fiat Lux Academe-Cavite, Philippines. The researchers made use of the Student's Anti-Intellectualism Scale and State Self-Esteem Scale to measure the two variables. Analyzed data revealed an average level of attitude of anti-intellectualism and a moderate level of self-esteem among the participants. Furthermore, there is a significant, inverse, and moderate correlation between the two variables (Pearson= -0.50; Spearman Correlation = -0.44). Thus, students with high level of self-esteem have low anti-intellectual attitudes. Conversely, students exhibiting low level of anti-intellectual attitudes tend to have higher self-esteem. The researchers also utilized other statistical techniques such as the t Statistic and linear regression.